2022
DOI: 10.1002/wrna.1735
|View full text |Cite
|
Sign up to set email alerts
|

Epi‐miRNAs: Modern mediators of methylation status in human cancers

Abstract: Methylation of the fundamental macromolecules, DNA/RNA, and proteins, is remarkably abundant, evolutionarily conserved, and functionally significant in cellular homeostasis and normal tissue/organism development. Disrupted methylation imprinting is strongly linked to loss of the physiological equilibrium and numerous human pathologies, and most importantly to carcinogenesis, tumor heterogeneity, and cancer progression. Mounting recent evidence has documented the active implication of miRNAs in the orchestratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 288 publications
0
2
0
Order By: Relevance
“…33 Focusing on BlCa, accumulating studies have reported cfDNA methylation as a potent biomarker for early diagnosis, prognosis, and monitoring of therapy responses. [34][35][36][37][38][39] In light of these findings, and along with the aberrant regulated levels of miR-143/145 in various malignancies and our previous published results on miR-143/145 cluster epigenetic regulation in bladder tumors, 19,40,41 we have studied the prognostic utility of MIR145 core promoter imprinting in pretreatment cfDNA.…”
Section: Discussionmentioning
confidence: 82%
“…33 Focusing on BlCa, accumulating studies have reported cfDNA methylation as a potent biomarker for early diagnosis, prognosis, and monitoring of therapy responses. [34][35][36][37][38][39] In light of these findings, and along with the aberrant regulated levels of miR-143/145 in various malignancies and our previous published results on miR-143/145 cluster epigenetic regulation in bladder tumors, 19,40,41 we have studied the prognostic utility of MIR145 core promoter imprinting in pretreatment cfDNA.…”
Section: Discussionmentioning
confidence: 82%
“…Most commonly, lncRNAs and circRNAs play roles in drug resistance by acting as miRNA sponges to regulate downstream gene expression [ 174 ]. “Epi-miRNAs” exert their effects by directly targeting epigenetic regulators, such as DNMTs and HDACs, or components of polycomb repressor complexes [ 175 ]. miRNAs affect mRNA transcription by binding to mRNA 3'-UTRs, leading to restoration of the expression of hypermethylated tumor suppressor genes [ 176 ].…”
Section: Mechanisms Of Drug Resistance In Ovarian Cancermentioning
confidence: 99%
“…Evidence indicates that multiple miRNAs are dysregulated in most types of cancer 25 . Recent reports suggest that altered levels of miRNAs are directly related to tumor progression [26][27][28] , evasion of the immune response 29,30 , epigenetic reprogramming 31,32 , and metastasis [33][34] . It has been demonstrated that tumor cells secrete a large number of exosomes loaded with various molecules, including miRNAs 36,37 .…”
Section: Perspective On Mirnas In the Context Of Cancermentioning
confidence: 99%